2022
DOI: 10.11124/jbies-21-00217
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ventilation tube insertion for conductive hearing loss in children with chronic otitis media with effusion and non-syndromic cleft palate: a systematic review protocol

Abstract: This review will investigate the efficacy of ventilation tube insertion versus non-surgical options in the management of chronic otitis media with effusion in children with non-syndromic cleft palate by assessing the degree of conductive hearing loss.Introduction: Chronic otitis media with effusion is common in children with cleft palate due to associated eustachian tube dysfunction. It can lead to impaired hearing and can hinder speech and language development. The main treatment options are drainage of effus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This systematic review was conducted in accordance with the JBI (formerly Joanna Briggs Institute) methodology for systematic reviews of effectiveness. 22 An a priori protocol 23 was developed and registered in PROSPERO (CRD42021255861). The protocol developed also sought to consider hearing aids but unfortunately the studies found considered both syndromic and non-syndromic participants with no distinction made in data analysis and thus this intervention was not included in the final review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was conducted in accordance with the JBI (formerly Joanna Briggs Institute) methodology for systematic reviews of effectiveness. 22 An a priori protocol 23 was developed and registered in PROSPERO (CRD42021255861). The protocol developed also sought to consider hearing aids but unfortunately the studies found considered both syndromic and non-syndromic participants with no distinction made in data analysis and thus this intervention was not included in the final review.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 236 articles were subjected to full text screening which resulted in exclusion of 232 articles based on requirements established in the protocol. 23 The final four articles were eligible for data extraction. [29][30][31][32][33][34]…”
Section: Study Inclusionmentioning
confidence: 99%
“…The review was conducted in accordance to JBI methodology for systematic reviews of effectiveness 9 and the protocol was registered with PROSPERO (CRD42021255861). 5 The outcomes of interest in the review were hearing thresholds, speech and language development and otological complications and these were informed by a study that integrated the views of clinical and non-clinical stakeholders in developing core outcomes sets for children with otitis media with effusion and cleft palate. 10…”
Section: Methodsmentioning
confidence: 99%
“…It is important that this condition is managed in a timely manner to ensure that the developmental milestones of these children are at par with their peers, as well as mitigating the associated costs to the public health system. 5 A recent systematic review conducted to determine the best management for chronic otitis media with effusion in children with non-syndromic cleft palate could not derive concrete conclusions regarding the most effective management. The review highlights the difficulties in evidence synthesis that are brought about by inconsistent and incomplete reporting of outcomes in observational studies, especially when reporting guidelines are not utilised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation